Haemorrhagic Transformation in Ischemic Stroke Induced by Polycythemia Vera: A Case Report - Zalafi Kartika Azka; Irfan Pranowo (Magna Neurologica, 2026)
Background: Polycythemia vera (PV) is a myeloproliferative neoplasm characterized by the overproduction of red blood cells. This can lead to hyperviscosity, which significantly increases the risk of thrombosis, which in turn increases the risk of ischemic stroke. There is currently no reported case of haemorrhagic transformation of PV-induced acute ischemic stroke in Indonesia. Case: A 62-year-old female was admitted to the emergency department after a sudden onset of left-sided weakness one hour before admission. She has a history of polycythemia vera, with prior hemoglobin levels reaching 22 g/dL, and had a previous ischemic stroke one year prior. On physical examination, the patient was alert, with a GCS of 15, blood pressure of 168/94 mmHg, left-sided hemiparesis, dysarthria, and facial drooping. Laboratory tests revealed elevated hemoglobin 16.8 g/dL, hematocrit 56%, platelets 466,000/µL, and leukocytes 20.4 x 10³/µL. A non-contrast head CT showed a hypodense lesion in the right temporoparietal lobe with a hyperdense spot, consistent with hemorrhagic transformation of a thromboembolic infarction in the right middle cerebral artery (MCA) region, an infarct in the left thalamus, and cerebral atrophy. Discussion: PV-induced ischemic strokes involve a confluence of hyperviscosity, endothelial activation, and platelet aggregation. The thickened blood compromises microcirculatory flow, particularly in the cerebral vascular, increasing embolic risks. HT occurs due to the reperfusion of ischemic tissues following the breakdown of the blood-brain barrier (BBB). Conclusion: Hemorrhagic transformation can develop in PV-induced acute ischemic stroke. Effective management requires a multidisciplinary approach, integrating acute stroke care, rigorous hematologic control, antihypertensive therapy, lifestyle modifications, and antiplatelet treatment.